Molecular signature of domestication in the arboviral vector Aedes aegypti - Lozada-Chávez, A.N.; Lozada-Chávez, I.; Alfano, N.; Palatini, U.; Sogliani, D.; Elfekih, S.; Degefa, T.; Sharakhova, M.V.; Badolo, A.; Patchara, S.; Casas-Martinez, M.; Carlos, B.C [UNESP]; et al. (Cold Spring Harbor Laboratory, 2023)
Abstract Background Domestication is a complex, multi-stage and species-specific process that results in organisms living close to humans. In the arboviral vector Aedes aegypti adaptation to living in proximity with anthropogenic environments has been recognized as a major evolutionary shift, separating a generalist form, Aedes aegypti formosus (Aaf), from the domestic form Aedes aegypti aegypti (Aaa), which tends to deposit eggs artificial containers and bite humans for a blood meal. These behaviors enhance the mosquito vectorial capacity. The extent to which domestication has impacted the Ae. aegypti genome has not been thoroughly investigated yet. Results Taking advantage of two forms’ distinct and historically documented geographic distributions, we analyzed the genomes of 634 worldwide Ae. aegypti mosquitoes. Using more than 300 million high-confidence SNPs, we found a unique origin for all out-of-Africa Ae. aegypti mosquitoes, with no evidence of admixture events in Africa, apart from Kenya. A group of genes were under positive selection only in out-of-Africa mosquitoes and 236 genes had nonsynonymous mutations, occurring at statistically different frequencies in Aaa and Aaf mosquitoes. Conclusion We identified a clear signal of genetic differentiation between Aaa and Aaf, circumscribed to a catalogue of candidate genes. These “ Aaa molecular signature ” genes extend beyond chemosensory genes to genes linked to neuronal and hormonal functions. This suggests that the behavioral shift to domestication may rely on the fine regulation of metabolic and neuronal functions, more than the role of a few significant genes. Our results also provide the foundation to investigate new targets for the control of Ae. aegypti populations.